Influence of Service Quality in Front of Member Loyalty to BMT Bif Jeroni, Bugisan, Yogyakarta - Safari, Teti; Turmudhi, Anis (Journal of Economics and Public Health, 2022)
This reaserch aims to find out how much service quality is to the loyalty of BMT BIF Jeroni 62 Bugisan Yogyakarta members. This research is quantitative research, using questionnaire data collection methods, with simple regression analysis that tests the research hypothesis. Based on the results of the analysis of data in this study shows that the quality of service has a positive effect on member loyalty has a value of 0.605 and significantly has a value of 0.000 or <0.05. Value Fcounts 14,927 > 2.32, hypothesis test F quality of service has a positive effect and is accepted or there is an influence of service satisfaction on the loyalty of financing members at BMT BIF Jeroni 62 Bugisan Yogyakarta. The value of the coefficient of determination R which indicates the degree of relationship between free variables and bound variables is 0.558 means that there is a strong relationship. R2 determination shows a large contribution of 0.311 or 31.1% of the quality of service to member loyalty.